Prior Activation of 5-HT7 Receptors Modulates the Conditioned Place Preference With Methylphenidate - Carbone, Cristiana; Lo Russo, Sara Lucia Maria; Lacivita, Enza; Frank, Annika; Alleva, Enrico; Stark, Holger; Saso, Luciano; Leopoldo, Marcello; Adriani, Walter (Frontiers in Behavioral Neuroscience, 2019)
The serotonin receptor subtype 7 (5-HT7R) is clearly involved in behavioral functions such as learning/memory, mood regulation and circadian rhythm. Recent discoveries proposed modulatory physiological roles for serotonergic systems in reward-guided behavior. However, the interplay between serotonin (5-HT) and dopamine (DA) in reward-related behavioral adaptations needs to be further assessed. TP-22 is a recently developed arylpiperazine-based 5-HT7R agonist, which is also showing high affinity and selectivity towards D1 receptors. Here, we report that TP-22 displays D1 receptor antagonist activity. Moreover, we describe the first in vivo tests with TP-22: first, a pilot experiment (assessing dosage and timing of action) identified the 0.25 mg/kg i.v. dosage for locomotor stimulation of rats. Then, a conditioned place preference (CPP) test with the DA-releasing psychostimulant drug, methylphenidate (MPH), involved three rat groups: prior i.v. administration of TP-22 (0.25 mg/kg), or vehicle (VEH), 90 min before MPH (5 mg/kg), was intended for modulation of conditioning to the white chamber (saline associated to the black chamber); control group (SAL) was conditioned with saline in both chambers. Prior TP-22 further increased the stimulant effect of MPH on locomotor activity. During the place-conditioning test, drug-free activity of TP-22+MPH subjects remained steadily elevated, while VEH+MPH subjects showed a decline. Finally, after a priming injection of TP-22 in MPH-free conditions, rats showed a high preference for the MPH-associated white chamber, which conversely had vanished in VEH-primed MPH-conditioned subjects. Overall, the interaction between MPH and pre-treatment with TP-22 seems to improve both locomotor stimulation and the conditioning of motivational drives to environmental cues. Together with recent studies, a main modulatory role of 5-HT7R for the processing of rewards can be suggested. In the present study, TP-22 proved to be a useful psychoactive tool to better elucidate the role of 5-HT7R and its interplay with DA in reward-related behavior.